A case study exploration of the therapeutic phenomena of projective identification, transference and countertransference: a brief therapy with a patient with psychotic anxiety - Abrahams, Deborah L (Department of Psychology, 2024)
This dissertation reviews the concepts of projective identification, transference and countertransference from an Object Relations theoretical perspective. The developmental mother-infant relationship is explored as a model for understanding the therapist-patient interaction in both its normal and pathological forms. Projective identification is used to illuminate the workings of transference and countertransference. W.R. Bion's conception of the mother-therapist as 'Container' and infant-patient as 'Contained' is presented as pivotal to understanding that interaction. Failures in projective identification - and therefore in symbolic functioning - are explored, with particular focus given to psychotic and psychosomatic manifestations in patients. The relevance of transference and countertransference phenomena to brief psychotherapy is also considered. These concepts are then applied to a specific therapeutic case. The patient was seen as an in-and outpatient over a 5 month period 1-3 times per week. The patient's history and a brief formulation are presented, followed by a discussion of how the above-mentioned theoretical issues manifested in the therapy. The patient operated on the border between psychosis and neurosis and communicated in primitive pre-verbal and powerful symbolic ways. Case illustrations focus on the interplay between her psyche and soma, the impact of the hospital setting as well as particular transference and countertransference difficulties incurred.